Mechanical properties of concrete containing Fly Ash, Rice Husk Ash and Waste Glass Powder - Salem Al-Ahdal, Basheer Mohammed; Xiong, Li Bi; Tufail, Rana Faisal (Civil Engineering Journal, 2018)
This paper for the first time investigates the workability, compressive and tensile strength of concrete containing Fly Ash, Rice Husk Ash and Waste Glass Powder. Seventy six cube specimen (150 150 150 mm were cast with different composition of Fly Ash, Rice Husk Ash ,Waste Glass Powder and steel fibers. The cubes were tested for axial compression and tensile tests. The research also investigated the effect of curing regime on the compressive and tensile strength of concrete cube specimen. The results revealed that the addition of 15 % Rice Husk Ash and 39% Fly Ash increased the workability of 25 % as compared to the controlled concrete. The sample containing 10 % Rice Husk Ash, 10% Waste Glass Powder and 39% micro silica produced worst workability as it decreased the workability up to 5 % of controlled concrete. The results for axial compressive strength shows that the addition of 15% Rice Husk Ash (RHA) and 39% of Fly Ash (FA) in concrete leads to the improvement of compressive strength by 14%. The sample containing replacement of 10% Rice Husk Ash (RHA), 10% waste glass powder (WGP) and 39 % of micro silica (MS) in concrete leads to the improvement by 53.9 for compressive. The replacement of 10% Rice Husk Ash (RHA), 10% waste glass powder (WGP ), 39 % of micro silica (MS) 3% steel fiber in concrete leads to the improvement by 37% for compressive strength. It was observed from the results of tensile strength that the samples containing 15% Rice Husk Ash (RHA) and 39 % of Fly Ash (FA) increased the tensile strength by 24% as compared to the controlled concrete. The sample containing replacement of 10% Rice Husk Ash (RHA), 10% waste glass powder (WGP) and 39 % of micro silica (MS) in concrete leads to an increase of 20% as compared to the controlled ones. Also, the replacement of 10% Rice Husk Ash (RHA), 10% waste glass powder (WGP), 39 % of micro silica (MS) 3% steel fiber increased the tensile strength by 40 % as compared to the controlled concrete sample. Finally, it was concluded that the replacement of 10% RHA, 39% micro Silica, 10% WG in concrete was found to be superior for increasing the mechanical properties of concrete.